Pengaruh Kelelahan Otot Tungkai Terhadap Biomekanika Pendaratan Pada Atlet Bola Voli - Finnasih; Rusdiana, Agus; Ikhwan Hidayat, Iwa; Kurniawan, Tian; Haryono, Tono (LPPM UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2024)
This study aims to analyze the impact of lower body fatigue on landing biomechanics in volleyball athletes, focusing on knee flexion angle, valgus/varus deviation angle, and the relationship between center of gravity (CG) and ground reaction force (GRF). A quantitative approach with a pretest-posttest design was employed. Thirteen volleyball athletes from the University’s sports club participated as samples. Biomechanical data were collected using cameras, force plates, and motion analysis software. Fatigue was induced through the Bosco test, and lactate levels were measured to confirm fatigue. The results showed that lower body fatigue significantly affected knee flexion angle (p = 0.003), while valgus/varus deviation angle (p = 0.540) and average CG-GRF (p > 0.05) showed no significant differences before and after fatigue. A negative and insignificant correlation was found between CG and GRF both before (r = -0.041, p = 0.893) and after fatigue (r = 0.098, p = 0.751). This study highlights the importance of neuromuscular training and lower body strengthening to reduce knee injury risks in volleyball athletes. Further research with more diverse protocols is needed to better understand these biomechanical mechanisms.